Investigation of the inhibitory effects of total flavonoids of litchi seed on Clonorchis sinensis-induced liver damage and fibrosis - Luo, Liuchun; Wang, Jilong; Cheng, Qiuchen; Lu, Zuochao; Lv, Jiahui; Xiao, Suyu; Tang, Lili; He, Shanshan; Liu, Dengyu; Tang, Zeli; Li, Qing; Zhan, Tingzheng (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundClonorchis sinensis (C. sinensis), which is prevalent in Asian countries, including China, Korea and Vietnam, is known to cause liver fibrosis, leading to various liver diseases and potentially fatal outcomes. Total flavonoids of litchi seed (TFL), a traditional Chinese medicine abundant in the Southern China, is known for its multiple pharmacological activities, including anti-fibrotic, anti-oxidative and hepato-protective properties. The present study explored the inhibitory effects of TFL on liver damage caused by C. sinensis infection in rats.MethodsIn the animal experiment, female rats were infected with C. sinensis and treated with TFL. Serum biochemical indicators were measured each week. Pathological changes in the rat liver were evaluated by examining the appearance of liver, and by performing hematoxylin and eosin (H&E) and Masson’s trichrome staining. Through immunofluorescence and immunohistochemistry, the number of activated hepatic stellate cells (HSCs) were counted and the collagen deposition area in these cells were measured. In the cell experiment, rat hepatic stellate cells (HSC-T6) were stimulated with TGF-β1 (10 ng/ml) and treated with different concentrations of TFL. The expression levels of HSCs activation markers α-smooth muscle actin (α-SMA), collagen I, and fibronectin were detected using quantitative real-time polymerase chain reaction (RT-qPCR). The protein levels of α-SMA and collagen I was detected by Western blot.ResultsTFL improved liver function in C. sinensis-infected rats, as indicated by reduced levels of transaminases, bilirubin, and bile acids. TFL also alleviated pathological changes in liver tissues. TFL also reduced the number of activated HSCs and downregulated fibrosis-related markers (collagen I/III, α-SMA) in rat liver. In HSC-T6, TFL inhibited HSCs activation by reducing the mRNA levels of α-SMA, collagen I, and fibronectin, and reduced the protein level of α-SMA and collagen I.ConclusionsTFL attenuated C. sinensis-induced liver fibrosis in rats. Our study provided experimental evidence for the development of novel anti-liver fibrosis drugs and offer new insights into the treatment of C. sinensis infections.